Obstetric violence and disability overlaps: obstetric violence during child birth among womens with disabilities: a qualitative study - Aregahegn Wudneh; Aneleay Cherinet; Mesfin Abebe; Yesuneh Bayisa; Nebiyu Mengistu; Wondwosen Molla (BMC, 2022)
Abstract Introduction Obstetric violence is an invisible wound which is being distorting the quality of obstetric care. Obstetric Violence, which is an issue spoken and amplified currently as a type of sexual violence and is of alarming seriousness and is an evolving field of inquiry despite women's experience of institutional childbirth, has garnered unprecedented global attention in recent years. Losing on both counts: obstetric violence is a double burden among disabled women. Aim To explore the experience of disabled women towards obstetric violence during child birth in Gedio zone, South Ethiopia. Methods Twenty-two (22) women with disabilities were interviewed. They were recruited through a nonprobability snowball sampling method. The interviews were conducted using a structured questionnaire in the Gedio zone, south Ethiopia. For coding purposes, NVivo (version 11) software was employed. Using a method known as continuous comparison, we classified the extracted codes based on their similarities and differences. The classes were then arranged in such a way that there was the greatest internal uniformity and the least external mismatch. Results The profile of the study group is predominantly of women between the ages of 21 and 30. Physical abuse, verbal abuse, stigma and discrimination, neglect and abandonment, and violations of privacy were the five major categories emerged during the thematic analysis describing the experience of obstetric violence. Women also observed these forms of obstetric violence among other disabled women during child birth. In addition to the violations of care, some of the participants described positive aspects of their childbirth experiences in one or more obstetric care settings. Conclusion This study concluded that the quality of service was deplorable, with reports of obstetric violence among this vulnerable group of women imposing a double burden on them. The findings suggest that there is a need to improve maternity care for disabled women by implementing comprehensive, culturally sensitive, client-sensitive special services and providing sensitivity training to healthcare providers, ensuring satisfied, equitable, and quality obstetric care.